Vapor-etching honeycomb-like zinc plating layer for constructing anti-corrosion lubricant-infused surfaces - Song, Xiaorui; Li, Na; Wang, Zhongshan; Li, Shuangjian; Hou, Yuanyuan (Frontiers in Chemistry, 2023)
Introduction: Biomimetic lubricant-infused porous surfaces are developed and applied for omniphobicity and corrosion protection, which exhibit great advantages compared to superhydrophobic surfaces. Methods: Herein, superhydrophobic Fe@E-Zn@PFOA was prepared via the electrodeposition of laminated Zinc coating, further vapor etching, and post-modification with perfluoro caprylic acid. The facile, inexpensive, and environment-friendly water vapor etching process can form a porous honeycomb-like structure. Moreover, the perfluoropolyether lubricant was wicked into the porous and superhydrophobic surfaces, obtaining lubricant-infused surfaces of Fe@E-Zn@PFOA@PFPE. Results and discussion: The influences of the textured roughness and chemical composition on the surface wettability were systematically investigated. The Fe@E-Zn@PFOA@PFPE performs omniphobicity with small sliding angles and superior corrosion resistance compared with the superhydrophobic surface, owing to their multiple barriers, including infused lubricant, hydrophobic monolayers, and compact Zn electroplating coating. Thus, the proposed lubricant-infused surface may provide insights into constructing protective coatings for the potential applications of engineering metal materials.